Does Chaos Matter in Financial Time Series Analysis? - Faggini, Marisa; Bruno, Bruna; Parziale, Anna (International Journal of Economics and Financial Issues, 2019)
The apparent randomness of financial market led some economists to approach chaos theory as a theoretical framework able to explain those fluctuations. This interest is because some nonlinear deterministic systems with few degrees of freedom create signals that mimic stochastic signals from the point of view of traditional time series analysis but with a deepener analysis performed by adequate tools could be chaotic. The aim of this paper is explorative in its nature, pointing to investigate chaos literature in order to grasp the difficulties typical of these applied researches and to see if something new is happening. Keywords: Chaos theory, time series, financial markets JEL Classifications: C1, G1, F65 DOI: https://doi.org/10.32479/ijefi.8058